1981
DOI: 10.1073/pnas.78.12.7281
|View full text |Cite
|
Sign up to set email alerts
|

Mutual interaction between adjacent dG . dC actinomycin binding sites and dA . dT netropsin binding sites on the self-complementary d(C-G-C-G-A-A-T-T-C-G-C-G) duplex in solution.

Abstract: The Watson-Crick imino protons, the backbone phosphodiester resonances, and the antibiotic exchangeable protons have been used as markers to monitor the separate and simultaneous binding of actinomycin and netropsin to the d(C-G-C-G-A-A-T-T-C-G-C-G) self-complementary duplex in aqueous solution. We demonstrate that intercalation ofactinomycin at dG(3'-5')dC sites at either end of the duplex results in a conformational perturbation at the dA-dT tetranucleotide core of the dodecanucleotide duplex. Parallel studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
32
0

Year Published

1983
1983
2008
2008

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 13 publications
5
32
0
Order By: Relevance
“…Our interpretation of this enhancement is that it is due to a conformational change in the DNA molecule induced by actinomycin D binding. This view is consistent with, data generated from NMR investiga- (20,21) and block copolymer studies (24), which support the argument that the binding of actinomycin D can affect DNA structure away from the primary binding sequence. Netropsin Binding.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…Our interpretation of this enhancement is that it is due to a conformational change in the DNA molecule induced by actinomycin D binding. This view is consistent with, data generated from NMR investiga- (20,21) and block copolymer studies (24), which support the argument that the binding of actinomycin D can affect DNA structure away from the primary binding sequence. Netropsin Binding.…”
supporting
confidence: 80%
“…All three sites are rich in G+C and contain the dimer 5'-G-C-3'. This observation is in accord with earlier studies (18)(19)(20)(21)(22)(23). It is interesting to note that other G-C sites are present between the observed binding sites but they are not occupied by actinomycin D. The significance of the 32-bp binding-site periodicity observed is unclear and requires further investigation.…”
supporting
confidence: 74%
“…Netropain is known to bind with a specificity for A•T regions in the minor groove of DNA duplexes (Zlmmer, 1975;Warteil et al, 1974). It has been shown that in the complex only one netropsin is bound per 12-mer duplex (Patel et al, 1981). Netropsin, which lacks a center of symmetry, removes the 2-fold symmetry of the 12-iner as revealed by up to a 0.02 ppm chemical shift difference for base pairs 3-6 on different ends of the helix (Patel et al, 1981).…”
Section: Spin-lattice Relaxation Versus Themical Exchangementioning
confidence: 99%
“…It has been shown that in the complex only one netropsin is bound per 12-mer duplex (Patel et al, 1981). Netropsin, which lacks a center of symmetry, removes the 2-fold symmetry of the 12-iner as revealed by up to a 0.02 ppm chemical shift difference for base pairs 3-6 on different ends of the helix (Patel et al, 1981). However, no measurable difference in the exchange lifetimes for individual base pairs on different ends of the 12-mer helix in the netropsin complex was observed.…”
Section: Spin-lattice Relaxation Versus Themical Exchangementioning
confidence: 99%
See 1 more Smart Citation